2019
DOI: 10.1159/000501636
|View full text |Cite
|
Sign up to set email alerts
|

Skin Care and Synbiotics for Prevention of Atopic Dermatitis or Food Allergy in Newborn Infants: A 2 × 2 Factorial, Randomized, Non-Treatment Controlled Trial

Abstract: <b><i>Background:</i></b> Atopic dermatitis (AD) and food allergy (FA) are common childhood diseases, which may either be interrelated or be the result of skin barrier disruption and gut mucosal dysbiosis. Although some evidence suggests the efficacy of emollients and synbiotics, there is no conclusive evidence on the use of these interventions alone or in combination. <b><i>Objectives:</i></b> This study is aimed at identifying the efficacy of emollients and syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 21 publications
0
74
0
6
Order By: Relevance
“…In infants at general risk, one trial examined synbiotics ( B bifidum OLB6378 plus fructo‐oligosaccharides) from birth to 6 months (food allergy prevalence at 1 year, RR: 1.03; CI: 0.63‐1.68, P > .05, low certainty) 63 …”
Section: Resultsmentioning
confidence: 99%
“…In infants at general risk, one trial examined synbiotics ( B bifidum OLB6378 plus fructo‐oligosaccharides) from birth to 6 months (food allergy prevalence at 1 year, RR: 1.03; CI: 0.63‐1.68, P > .05, low certainty) 63 …”
Section: Resultsmentioning
confidence: 99%
“…Both studies showed no significant reduction in the incidence of AD, and in the BEEP study, there was an increased rate of infections and a trend toward increased food allergy in the intervention group 113,114 . Similarly, an RCT by Dissanayake et al compared the incidence of AD and FA in the first year of life in infants treated with synbiotics and an emollient (alone or in combination) and controls and found no statistical difference 163 . The negative findings in these studies were surprising given the pilot study findings, and the authors discussed various reasons as to why this might have occurred including low adherence rate with the intervention (especially PreventADALL), contamination of the control arm (BEEP), and the type of emollient used.…”
Section: The Role Of Emollients To Prevent the Development Of Food Allergymentioning
confidence: 99%
“…Reasons for the inconsistency in results for moisturizer interventions might be due to different countries and cultures, different types of moisturizers, and differences in adherence. Dissanayake et al [18] performed an RCT in Japan to examine whether combined synbiotics and skin moisturizers could prevent AD and food allergy. However, they did not show e cacy of moisturizer application two to three times/day against prevention of AD and food allergy.…”
Section: Discussionmentioning
confidence: 99%